Inflammatory mechanism of Rumenitis in dairy cows with subacute ruminal acidosis - Zhao, Chenxu; Liu, Guowen; Li, Xiaobing; Guan, Yuan; Wang, Yazhou; Yuan, Xue; Sun, Guoquan; Wang, Zhe; Li, Xinwei (BMC veterinary research, 2018)
Subacute ruminal acidosis (SARA) is a metabolic disease in high-producing dairy cattle, and is accompanied by rumenitis. However, the mechanism of rumenitis remains unclear. Therefore, the aim of this study was to investigate the molecular mechanism of rumenitis in dairy cows with SARA. The results showed that SARA cows displayed high concentrations of ruminal volatile fatty acids, lactic acid and lipopolysaccharide (LPS). Furthermore, the blood concentrations of LPS and acute phase proteins haptoglobin, serum amyloid-A, and LPS binding protein were significantly higher in SARA cows than in control cows. Importantly, the phosphorylation levels of nuclear factor-kappaB (NF-κB) p65, inhibitor of NF-κB (IκB), c-Jun N-terminal kinase (JNK), and extracellular signal-regulated kinase 1/2 (ERK1/2) were significantly higher in the rumen epithelium of SARA cows than those of control cows. The ruminal mRNA and protein levels of NF-κB- and mitogen-activated protein kinase (MAPK)s -regulated inflammatory cytokines, tumor necrosis factor α (TNF-α), interleukin 6 (IL-6) and interleukin 1β (IL-1β), were markedly higher in SARA cows than in control cows. Similarly, serum concentrations of TNF-α and IL-6 were also significantly higher in SARA cows. These results indicate that SARA results in high concentration of ruminal LPS, which over activates the NF-κB and MAPKs inflammatory pathways and then significantly increases the expression and synthesis of pro-inflammation cytokines in the rumen epithelium, thereby partly inducing rumenitis.